2012
DOI: 10.1155/2012/548157
|View full text |Cite
|
Sign up to set email alerts
|

Florbetaben PET in the Early Diagnosis of Alzheimer's Disease: A Discrete Event Simulation to Explore Its Potential Value and Key Data Gaps

Abstract: The growing understanding of the use of biomarkers in Alzheimer's disease (AD) may enable physicians to make more accurate and timely diagnoses. Florbetaben, a beta-amyloid tracer used with positron emission tomography (PET), is one of these diagnostic biomarkers. This analysis was undertaken to explore the potential value of florbetaben PET in the diagnosis of AD among patients with suspected dementia and to identify key data that are needed to further substantiate its value. A discrete event simulation was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 34 publications
0
30
1
Order By: Relevance
“…This allows an earlier diagnosis with a high level of confidence. Economic models have suggested that shortening the time to diagnosis of AD by confirming the presence of AD pathology with FBB PET may be cost-effective 29. There was an excellent inter-rater reliability for the visual reads as well as an almost perfect concordance with the classification of a scan as positive or negative for Aβ by semiquantitative assessment with the neocortical SUVR, supporting its use in routine clinical settings.…”
Section: Discussionmentioning
confidence: 85%
“…This allows an earlier diagnosis with a high level of confidence. Economic models have suggested that shortening the time to diagnosis of AD by confirming the presence of AD pathology with FBB PET may be cost-effective 29. There was an excellent inter-rater reliability for the visual reads as well as an almost perfect concordance with the classification of a scan as positive or negative for Aβ by semiquantitative assessment with the neocortical SUVR, supporting its use in routine clinical settings.…”
Section: Discussionmentioning
confidence: 85%
“…Sixteen studies concerning the clinical utility of amyloid PET imaging were found in the literature (17,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Supplemental Table 3 summarizes these studies.…”
Section: Clinical Utility Of Amyloid Imagingmentioning
confidence: 99%
“…However, 3 model simulation studies on that topic have been published: Guo et al (36) modeled the outcome effect of 18 F-florbetaben in predementia and dementia subjects. For both subgroups, that study found that amyloid imaging brought about estimated gains of 0.27 and 0.03 in quality-adjusted life years (QALYs; a measure combining the quality and the quantity of life lived), as compared with a scenario without amyloid imaging.…”
Section: Impact Of Amyloid Imaging On Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The few available models starting in predementia stages of AD commonly assume a relative risk reduction of conversion to dementia in subjects on treatment, followed by a simulation model of disease progression throughout the dementia stages [44,[51][52][53]. However, conversion to both MCI and dementia are uncertain and highly dependent on the study methods.…”
Section: Modelling Conversion To Dementiamentioning
confidence: 99%